Primary hyperparathyroidism in multiple endocrine neoplasia type 1: when to perform surgery? - Giusti, Francesca (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2012)
Primary hyperparathyroidism is a common endocrinological disorder. In rare circumstances, it is associated with familial syndromes, such as multiple endocrine neoplasia type 1. This syndrome is caused by a germline mutation in the multiple endocrine neoplasia type 1 gene encoding the tumor-suppressor protein menin. Usually, primary hyperparathyroidism is the initial clinical expression in carriers of multiple endocrine neoplasia type 1 mutations, occurring in more than 90% of patients and appearing at a young age (20–25 years). Multiple endocrine neoplasia type 1/primary hyperparathyroidism is generally accompanied by multiglandular disease, clinically manifesting with hypercalcemia, although it can remain asymptomatic for a long time and consequently not always be recognized early. Surgery is the recommended treatment. The goal of this short review is to discuss the timing of surgery in patients when primary hyperparathyroidism is associated with multiple endocrine neoplasia type 1.